Speed and heart rate variation during marathon running in a hot environment - Rojas-Valverde, Daniel (Escuela de Educación Física y Deportes - Universidad de Costa Rica, 2020)
The purpose of the study was to analyze the variation of running speed and heart rate in amateur runners during a marathon in a hot environment. Eighteen runners (weight: 65.2 ± 12.21 kg, height: 168.4 ± 10.6 cm, VO2max: 52.9 ± 7.1 ml/kg/min) took part of a beach-side marathon (42195 m) under a temperature of 27.8 ± 3.52 ºC and at 0-80 m altitude. Pearson’s correlation showed a significant linear relationship between the increase in thermal stress index (WGBT) and the speed variation (r= 0.168, p= 0.049). In this respect, the total duration of the race revealed a direct relationship with speed (r= 0.675, p= 0.003) and heart rate (r= 0.631, p= 0.007) variation. Multiple regressions analysis showed that 61.6% of the final race time was explained by the speed variation in the 26 to 30 km course section (r2= 0.61; F= 26.17; p< 0.001) and 37% by the heart rate variation in the 31 to 35 km section (r2= 0.37; F= 10.38; p< 0.001). In conclusion, an increase in the environmental temperature provoked a decrease in running pacing, with a stronger effect in the second half of the race. Therefore, coaches should take these aspects into account in training and strategies to mitigate the impact of these conditions on the physical and physiological performance of amateur runners.